EFECTO CICATRIZANTE DEL CHAMPÚ LÍQUIDO DE Colletia spinosissima J. GMELIN “TACSANA” EN RATONES - Herrera, Beatriz (2014)
The objective of the study was to determine the healing effect of Colletia spinosissima (tacsana) shampoo based on induced injuries in mouse skin. Were used 36 albino mice, weighing between 30-35 g; to which was depilated in the dorsal area, applying lidocaine gel 4% in the depilated area to induce lesions (wounds) on the skin. The animals were allocated into five groups, each group consisting of six mice. The experimental design was composed as follows: G1: negative control, G2: positive control; G3, G4 and G5 formulated 10%; 20%; and 30%, respectively; G6: Pantene®. The liquid shampoo was administered twice daily for fourteen consecutive days. Results shows that in groups 4 and 5 was reduced the injury to the skin on the fourth day, the animals of group 5 exhibited a process of scabs and skin repair, with collagen formation in the histological study. It is concluded that liquid based shampoo Colletia spinosissima (tacsana) provided 30% healing effect in mouse skin induced injuries.